2014
DOI: 10.1021/la404110y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adsorption of Gold Nanoparticles to Gold/Palladium and Platinum Surfaces

Abstract: Integration of molecule-capped gold nanoparticles (AuNP) into nanoelectronic devices requires detailed knowledge about the AuNP-electrode interface. Here, we report the pH-dependent adsorption of amine or carboxylic acid-terminated gold nanoparticles on platinum or gold/palladium (30% Pd) alloy, respectively. We synthesized amine-terminated AuNP, applying a new solid phase supported approach, as well as AuNP exhibiting carboxylic acid as terminal groups. The pH-induced agglomeration of the synthesized AuNP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 45 publications
1
29
0
2
Order By: Relevance
“…Furthermore, as already previously reported in our work on isotropically functionalized AuNP and investigations on molecule/metal junctions, these selected molecular terminal group/metal combinations should allow us to control the directionality of Janus-AuNP immobilization. 26,31 The resulting device Pt-MPA/AuNP/MOA-AuPd should ideally exhibit an asymmetry of the measured I/U characteristic. Furthermore, if directed immobilization is successful, i.e., MPA is always bound to the Pt electrode and MOA is always bound to the AuPd electrode, like suggested from XP-spectroscopy, the asymmetry of the I/U characteristic should be in the same direction for all devices.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Furthermore, as already previously reported in our work on isotropically functionalized AuNP and investigations on molecule/metal junctions, these selected molecular terminal group/metal combinations should allow us to control the directionality of Janus-AuNP immobilization. 26,31 The resulting device Pt-MPA/AuNP/MOA-AuPd should ideally exhibit an asymmetry of the measured I/U characteristic. Furthermore, if directed immobilization is successful, i.e., MPA is always bound to the Pt electrode and MOA is always bound to the AuPd electrode, like suggested from XP-spectroscopy, the asymmetry of the I/U characteristic should be in the same direction for all devices.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Adsorption of Au-MOA and Au-AOT on Pt and AuPd surfaces in dependence of the addition of different monovalent chloride salts Au-MOA nanoparticles with a mean diameter of 13.1 nm AE 1.3 nm were synthesized from citrate stabilised AuNPs by a ligand exchange reaction with MOA as previously published, 17 puried by centrifugation and redispersed in HEPES/TRIS buffer at pH 9. For the synthesis of Au-AOT (mean diameter 14.9 nm AE 1.2 nm) a solid phase supported approach was applied in order to prevent irreversible aggregation of the citrate stabilised AuNPs during ligand exchange with AOT.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond this, we investigated the differential adsorption of ligand stabilised AuNP on pristine gold (alloyed with 30% palladium due to the manufacturing process) and platinum surfaces depending on the pH and the ionic strength of the immobilisation solution. 17 We found that mercaptooctanonic acid (MOA) functionalised AuNPs (Au-MOA) at pH 9 and 1,8aminooctanethiol (AOT) stabilised AuNPs (Au-AOT) at pH 3 adsorb on platinum surfaces with high selectivity (Fig. 1b).…”
Section: Introductionmentioning
confidence: 92%
“…The UV–vis spectrum exhibits the typical plasmon peak at 525 nm for a spherical AuNP with an average size of 15 nm ( Figure 5 c). The carboxylic acid group of the MPA–AuNP is deprotonated and therefore negatively charged at pH 5 and higher, while at pH <5, protonation of the carboxylic end groups occurs, which leads to an aggregation of the particles in the acidic media, similar to mercapto-octanoic acid stabilized AuNP [ 41 ].…”
Section: Resultsmentioning
confidence: 99%